PENGARUH UKURAN PERUSAHAAN, KEBIJAKAN DIVIDEN, KEBIJAKAN LEVERAGE, KEPEMILIKAN MANAJERIAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA INDEKS LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mursidah Nurfadillah; Vera Anitra (Jurnal Ekonomi STIEP, 2020)
This study aims to analyze the effect of company size, dividend policy, leverage policy, managerial ownership and profitability on firm value on the LQ 45 index listed on the Indonesia stock exchange. The technique of collecting time series data for five years is from 2013 to 2017, by analyzing the LQ 45 company’s annual report. This type of research is included in causal research with quantitative methods, and data analysis techniques using multiple linear regression. The results of the analysis show that simultaneous company size, dividend policy, leverage policy, managerial ownership and profitability have a significant effet on firm value, whereas only partially only company size have a significant effect.